2008
DOI: 10.1007/s10620-008-0465-x
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Expression of Peroxisome Proliferator-Activated Receptor Delta and Cyclooxygenase-2 May Enhance Angiogenesis and Tumor Venous Invasion in Tissues of Colorectal Cancers

Abstract: We conducted this study to evaluate the impact of the expression of peroxisome proliferator-activated receptor delta on angiogenesis in tissue samples of colorectal cancer. We examined 52 samples of primary human colorectal carcinomas and matched normal adjacent tissues to evaluate the expression of peroxisome proliferator-activated receptor delta, cyclooxygenase-2, vascular endothelial growth factor-A, and CD34 through immunohistochemical analysis. Peroxisome proliferator-activated receptor delta was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…This finding is consistent with the studies by Takayama and colleagues (8) and Yoshinaga and colleagues (29). The specificity of the PPAR d antibody in the present study was verified by Western blot, which showed a clear band at the expected position of PPAR d protein as shown in Figure 1C.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with the studies by Takayama and colleagues (8) and Yoshinaga and colleagues (29). The specificity of the PPAR d antibody in the present study was verified by Western blot, which showed a clear band at the expected position of PPAR d protein as shown in Figure 1C.…”
Section: Discussionsupporting
confidence: 94%
“…The selective PPAR δ agonist GW501516 acts as a tumor promoter in mammary carcinogenesis [19] and colon tumorigenesis [15, 20, 21], whereas disruption of PPAR δ expression blocks mammary [22] and colon tumorigenesis [23, 24]. PPAR δ is regulated by risk factors implicated in cancer progression, including K-Ras [25], Wnt [26], and Pges/Cox2 [22, 27], and is associated with activation of angiogenesis [20, 2830]. PPAR δ regulates proinflammatory signaling through NF κ B and IL-1 β [31], and is activated by metabolites of arachidonic acid metabolism that serve as PPAR ligands [14, 29, 32].…”
Section: Introductionmentioning
confidence: 99%
“…The proangiogenic properties of PPAR β / δ make this nuclear receptor a new pharmacological target to face ischemic events which may affect heart [69, 70] and brain [71] but also other tissues such as kidney [72]. Regarding tumoral growth, physiological proangiogenic properties of PPAR β / δ might be regarded as undesired properties, potentially strengthening metabolic coupling between tumor and its stroma, and several experimental and clinical reports have incriminated a positive link between PPAR β / δ and tumoral cell growth [7376]. However, recent evidence highlights that PPAR β / δ and its ligands may also convey, on the opposite, antiangiogenic properties [77, 78].…”
Section: Ppars Inflammation Angiogenesis and Warburg's Effectmentioning
confidence: 99%